Letter: Juggling Career and Children - Uta Frith (Opticon1826, 2008)
Since I received the RCUK Award for Women of Outstanding Achievement in Science, Engineering, and Technology earlier this year, I have been frequently asked about my views on combining a scientific career with having a life. Perhaps I might take this opportunity to address those among your readers who may have the same question.
Keywords: academia; women